A teoria de mundo-próprio de Jakob Von Uexkull : entre a metafísica e o naturalismo - Souza, Elaine Cristina Borges de (2012)
This work proposes to analyze the philosophical meanig of the theory of "self-world" (in German, Umwelt) devoloped by the biologist Jakob Von Uexkull. Among different interpretations proposed by important philophers, the theory is situted between an eventual metaphysics and a particular form of naturalism regarding to the way how different lived organisms perceive and act on the environment. To make possible this study, this work is divided in tree chapters. The fist on is dedicated to an analysis on the wide influence that Uexkull had from Kant s ideas and that indicates the philosophical basis of his theoretical biology. In the second chapter, we will analyze Heidegger interpretation that understands the theory of self-world in a particular metalphisical meaning. In the third chapter, we will examine the interpratation that understands the theory of sel-world as an altenative form of naturalism which breaks away the cartesian dualism in Merleau-Ponty view. From this showing, it is proposed to evaluate the eventual interpretations for the theory of self-world and their philosophical consequences.